Taffe Kommissarinnen und emanzipierte Kommissare?: Zur sozialen Konstruktion zeitgenössischer TV-Ermittlerteams in deutschen Krimiserien - Tkotzyk, Raphaela (transcript, 2017)
"Doppelter Einsatz" (Double the stakes) for gender studies: How traditional gender roles are (re)produced and/or rearranged in investigative teams featured in German crime series.